As trajetórias de jovens em situação de pobreza na Universidade: uma avaliação da política de cotas na Universidade Federal do Ceará - Sousa, Vladinise Pinheiro de (2020)
This study aims to present an evaluation of the Quota Policy in the context of the Universidade Federal do Ceará, based on the experiences of students who benefited by said policy, specifically those favored by quotas for students coming from public schools and who have a family income equal to or less than 1,5 times the minimum wage per person. To obtain these experiences, two UFC courses were chosen, considered to be highly socially prestigious, namely, Medical and Law schools. The choice of such courses is due to the historical representation of Medical and Law schools as the most disputed ones in university admission exams, and consequently, with a significant presence of students from the most economically favored classes. In each course, one student from each academic year, who entered university through the L1 Quota, was interviewed, covering the period from 2014 to 2019, totalizing 14 interviewed students. As an evaluation proposal for the policy in question, thisstudy rested on the counter-hegemonic perspective of evaluation, focused onthe analytical axes of In-Depth Evaluation, conceived by Rodrigues (2008) and founded on Lejano’s (2012) hermeneutic paradigm. This is a research with a qualitative approach, inserted in the field of social research, making use of techniques such as bibliographic, documentary and field research. In order to achieve the proposed objectives, documentary research was carried out in the policy’s official documents, with the purpose of enabling an analysis of the main regulations that govern the implementation of the quota system. As a data collection instrument, semi-structured interviews were conducted with the research’s fundamental actors, namely, students who entered university through the L1 Quota.Some qualitative indicators were pointed out based on the evaluation carried out and according to the interlocutors’ statements. It was found that the policy has been an achievement for public school students, trickling down to their families and the environment to which they belong. In addition, it has given representation in the academic environment to socially marginalized groups, who do not hold political power. Notwithstanding the Quota Policy’s contribution to the integration of these segments in academia, the need to present conditions of permanence was highlighted, taking into account the multiple forms of poverty that students find themselves in, which go beyond the issue of admission to university.